Assessing public participation initiatives in local government decision-making in Malaysia - Abdul Manaf, Halimah; Mohamed, Ahmad Martadha; Lawton, Alan (Taylor & Francis Group, 2016)
Increased public participation in government decisions contributes significantly to the enhancement of grass-roots democracy.This article assesses the level of involvement of local citizens in local government decisions in Malaysia.Public participation was assessed using questionnaires on the range and extent of initiatives used by local government. The questionnaires also probed citizens’ perceptions of these initiatives and expectations for greater citizen empowerment.Data were gathered from 206 local citizens randomly selected from six local authorities in the northern region of Malaysia. The findings reveal a desire on the part of local citizens to participate in their local government decision-making process.